Bulk Heterojunction Formation between Indium Tin Oxide Nanorods and CuInS2 Nanoparticles for Inorganic Thin Film Solar Cell Applications - Cho, Jin Woo; Park, Se Jin; Kim, Jaehoon; Kim, Woong; Park, Hoo Keun; Do, Young Rag; Min, Byoung Koun (American Chemical Society, 2012)
In this study, we developed a novel inorganic thin film solar cell configuration in which bulk heterojunction was formed between indium tin oxide (ITO) nanorods and CuInS2 (CIS). Specifically, ITO nanorods were first synthesized by the radio frequency magnetron sputtering deposition method followed by deposition of a dense TiO2 layer and CdS buffer layer using atomic layer deposition and chemical bath deposition method, respectively. The spatial region between the nanorods was then filled with CIS nanoparticle ink, which was presynthesized using the colloidal synthetic method. We observed that complete gap filling was achieved to form bulk heterojunction between the inorganic phases. As a proof-of-concept, solar cell devices were fabricated by depositing an Au electrode on top of the CIS layer, which exhibited the best photovoltaic response with a V-oc, J(sc), FF, and efficiency of 0.287 V, 9.63 mA/cm(2), 0.364, and 1.01%, respectively.
Keywords: POLYMER PHOTOVOLTAIC CELLS; NANOCRYSTAL INKS; EFFICIENCIES; DEPOSITION; GROWTH; DEVICE